Customer Satisfaction and Loyalty of Mcross Barbershop - Alfiandi, Vito Aldriansyah; Sumiyati, Sumiyati (Borong Newinera Publisher, 2025)
In today's era, the business world is growing very rapidly, one of which is in the field of barbershops. In recent years, barbershops have gained significant popularity in various parts of the world, including Indonesia, one of which is in Pontianak City. Seeing the need for haircut services for men is quite in demand, the haircut business specifically for men has become a business opportunity that can provide benefits. Therefore, researchers, researchers conducted a study and research on customer satisfaction and loyalty of MCROSS barbershop in Pontianak City. In this scientific paper, the research method used is associative research. Based on the results obtained from the study, the author can conclude the Effect of Service Quality on Customer Satisfaction Testing the direct effect between Service Quality and Customer Satisfaction obtained a t-statistic value of 5.781 with a p-value of 0.000. This shows that there is a direct effect between Service Quality and Customer Satisfaction. So it can be said that H1, namely Service Quality has a positive and significant effect on Customer Satisfaction, is accepted.